Sacramental and spiritual use of hallucinogenic drugs - Moro L; Noreika V (CAMBRIDGE UNIV PRESS, 2022)
Arguably, the religious use of hallucinogenic drugs stems from a human search of metaphysical insight rather than from a direct need for cognitive, emotional, social, physical, or sexual improvement. Therefore, the sacramental and spiritual intake of hallucinogenic drugs goes so far beyond other biopsychosocial functions that it deserves its own category in the drug instrumentalization list.